KUALITAS AUDIT PADA MASA PENERAPAN KEBIJAKAN WORK FROM HOME PANDEMI COVID-19 PADA KAP JAKARTA - Yanny; Prasetyo, Arihadi (Lembaga Penelitian dan Pengabdian kepada Masyarakat Institut Bisnis dan Informatika Kwik Kian Gie, 2022)
This research aims to find out the effect of independence, integrity and professional ethics on the audit quality of KAP Central Jakarta and South Jakarta when implementing work from home (WFH) policies during the COVID-19 pandemic. We used used purposive sampling technique for the purpose data collection. This study used 40 samples of Auditor Accounting Firm. Data testing was conducted using IBM SPSS Statistics version 26. Hypothesis testing in this study is conducted with the F test, the t statistical test, the determination coefficient test and the multiple regression analysis test. The results showed that variable independence didn’t have a significant positive effect on the audit quality of KAP Central Jakarta and South Jakarta at the time of WFH policy, while variable integrity and professional ethics positively significant effect on the audit quality in Central and South Jakarta KAP’s Firm during implementation of WFH policy.